Soluble interleukin-1 receptor type 2 plasma levels in Parkinson’s disease: relationship with cardiac autonomic profile before and after peripheral mechanical somatosensory stimulation - Shiffer, Dana; Zamunér, Antonio Roberto; Minonzio, Maura; Bulgheroni, Mara; Porta, Alberto; Leone, Roberto; Bottazzi, Barbara; Garlanda, Cecilia; Colotta, Francesco; Barbic, Franca; Mantovani, Alberto; Furlan, Raffaello (Frontiers in Physiology, 2023)
Systemic inflammation promotes neurodegeneration in Parkinson's disease (PD). Interleukin-1 receptor type 2 (sIL-1R2) plasma levels increase during inflammation. Data on sIL-1R2 in PD patients and its relationship with PD cardiac autonomic profile are limited, given the possible antiinflammatory effect of vagal activation. Previously, automated mechanical peripheral somatosensory stimulation (AMPSS) enhanced cardiac vagal modulation. Objectives were to 1) evaluate sIL-1R2 plasma concentrations in PD patients and healthy controls and 2) investigate the correlations between sIL-1R2 and cardiac autonomic indices obtained by spectrum analysis of heart rate variability before and after AMPSS. sIL-1R2 plasma levels were assessed in 48 PD patients and 50 healthy controls.Electrocardiogram and beat-by-beat arterial pressure were recorded at baseline and after 5 AMPSS sessions in 16 PD patients. PD patients had higher sIL-1R2 levels than controls. In the PD subgroup, an inverse correlation between sIL-1R2 and HFnu was found. There was a negative correlation between changes induced by AMPSS on HFnu and sIL-1R2. Higher sIL-1R2 levels in PD patients reflect the inflammatory dysregulation associated with the disease. In PD patients, higher sIL-1R2 was associated with reduced cardiovagal tone. Increased cardiovagal modulation following AMPSS was associated with lower sIL-1R2 levels in Parkinson's disease patients, suggesting inflammatory state improvement.